PARENTAL GUIDANCE IN DEVELOPING INTEREST IN LEARNING TO MEMORIZE KORAN IN TKQ (KINDERGARTEN OF ALQURAN) IN MEDAN DISTRICT OF MARELAN - Aisyah Richza Adya Lubis, Saiful Akhyar Lubis, Edi Saputra (At-Tazakki: Jurnal Kajian Ilmu Pendidikan Islam dan Humaniora, 2019)
Abstract: This research is motivated by the number of children who tend to spend their free timeto play, and most fathers and mothers are preoccupied with work. There are children who livewith servants, wander with friends, or stay at home while watching television, video games,playstation. This is one of the main factors that causes a low quality of interaction between them.The purpose of this study is to analyze Parental Guidance in Developing Learning Interests inMemorizing Koran at Zakhira TKQ Medan Marelan Subdistrict. This study uses a DescriptiveQualitative Method, carried out at Zakhira T.600 TKQ Medan Marelan District. The subjects ofthis study were parents of TKQ Zakhira students, who were informants were parents, studentsand TKQ Zakhira teachers. Data was collected using interview, observation, and documentationmethods. The results of this study were that parental guidance for children in memorizing theKoran at Zakhira TKQ in Medan Marelan Sub-district included the following: 1. Parents as guidelines,parents also tried to memorize the Koran, and provide examples of correct reading to children; 2.Parents as child motivators, parents tell the importance of memorizing the Koran and giving gifts;3. Parents as mentors, parents mentally educate children and justify memorizing children if thereare incorrect readings; 4. Parents as child facilitators, parents take the time to accompany childrento memorize the Koran and create a conducive environment; 5. Parents as managers forchildren, parents determine muraja’ah schedules and children’s memorization targets.Keywords: Guidance, Study Interest, Koran, TKQ